KELAYAKAN POTENSI SUMBER DAYA ENERGI TERBARUKAN SEBAGAI SOLUSI KETERBATASAN DAYA LISTRIK DI PEDESAAN DENGAN METODE SEL SURYA - Bambang Setyo Panulisan; Wiwien Suzanti; Yolla Sukma Handayani; Basuki Rakhim Setya Permana; Dedy Khaerudin; Asih Setyo Rini; Asep Rahmatullah (Indonesian Journal of Thousand Literacies, 2023)
Looking for alternatives to obtain electricity resources in remote areas is considered necessary when community activities can be disrupted, education, economy and living standards can be affected due to lack of electricity. The stability of the feed must be ensured. Electricity consumption is an important need of today's society. The lives of urban communities and their supporting electric power areas are not a problem with the continuity of services of the State Electricity Company (PLN). . In rural communities living in remote areas and on remote islands, electricity supply is a problem in itself. Given that the availability of the national electricity grid is not long-term, the solution to overcome the saturation of regional electrical energy is to convert sunlight into electrical energy using photovoltaic technology (solar cells). The system of providing electrical energy using this system is called Solar Power Plant (PLTS). Solar allows the use of the solar home system method "SHS". This analysis is expected to be a reference for the use of SHS or for electricians to find out the suitability between energy needs, prices and quality of solar cells for residential use